2015
DOI: 10.1021/ma502352x
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Strong Blue Photoluminescence Produced from the Aggregation of Unconventional Chromophores in Novel Siloxane–Poly(amidoamine) Dendrimers

Abstract: Poly­(amidoamine) (PAMAM) dendrimers and hyperbranched poly­(amidoamine)­s are the first reported and most investigated luminescent polymers containing unconventional chromophores. The luminescence of these compounds is associated with the N-branched tertiary amine moiety, and the oxidation of the tertiary amine is assigned to the emitting source. However, in this paper, a series of novel siloxane–poly­(amidoamine) (Si-PAMAM) dendrimers were synthesized by aza-Micheal reaction, and strong blue photoluminescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
149
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 188 publications
(159 citation statements)
references
References 20 publications
8
149
1
1
Order By: Relevance
“…[37][38][39] From the traditional point of view, chromogenfree compounds rarely exhibit strong fluorescence; a few exceptions, however, have been covered recently, and they are those possessing dendritic or hyperbranched architecture, such as poly(amidoamine) (PAMAM), [40][41][42][43] polyureas (PURE), 44 hyperbranched phosphate (HBPP), 45 poly(ether amide)s (PEA), 46 poly-(propyleneimine) (PPI) 47 and poly(amino ester) (PAE). 52 We also reported new watersoluble hyperbranched polysiloxanes (WHPSs) contemporaneously bearing hydroxyl and primary amine groups, and the result shows that the terminal hydroxyl group rather than primary amine group in WHPSs plays a critical role in producing the blue-luminescent species. It is well recognized that the oxidation or acidification of the tertiary amine in PAMAM, PURE, PEA, PPI, PAE, PVP and PEI should lie behind the light emission.…”
Section: Introductionmentioning
confidence: 89%
“…[37][38][39] From the traditional point of view, chromogenfree compounds rarely exhibit strong fluorescence; a few exceptions, however, have been covered recently, and they are those possessing dendritic or hyperbranched architecture, such as poly(amidoamine) (PAMAM), [40][41][42][43] polyureas (PURE), 44 hyperbranched phosphate (HBPP), 45 poly(ether amide)s (PEA), 46 poly-(propyleneimine) (PPI) 47 and poly(amino ester) (PAE). 52 We also reported new watersoluble hyperbranched polysiloxanes (WHPSs) contemporaneously bearing hydroxyl and primary amine groups, and the result shows that the terminal hydroxyl group rather than primary amine group in WHPSs plays a critical role in producing the blue-luminescent species. It is well recognized that the oxidation or acidification of the tertiary amine in PAMAM, PURE, PEA, PPI, PAE, PVP and PEI should lie behind the light emission.…”
Section: Introductionmentioning
confidence: 89%
“…[6,19] Some reports attributed the emission to aggregation of carbonyl groups. [20] In the case of hyperbranchedp olyether epoxy,t he aggregation of the highly dense epoxy groups were responsible for fluorescencee mission. [12] However,t hesem echanismsw ere too specific to summarize the fluorescence emission for all of the nonconventional luminogens.…”
Section: Hang Lumentioning
confidence: 99%
“…Previous reportsh ave shown that the structural features of fluorescent polymers, dendrimers or supramolecular assemblies can easily make the nonconventional chromophores aggregated to form extended conjugation because of chain entanglement, dendritic effect, and intermolecularf orces. [11,20] Compared to these polymers, the presents iloxane derivatives are small and simple. In other words, the molecules should be theoretically monodispersed in dilute solutions, andt he conjugation should not be bulky enough to emits trong fluorescence.H owever, simple siloxane derivatives, including BSCN, BSMA and Si-PAMAM( Figure S5,S upporting Information), can emit bright blue fluorescence in dilute solutions.…”
Section: Hang Lumentioning
confidence: 99%
See 2 more Smart Citations